Metascience in Bioinformation - Khakshooy, Allen (Bioinformation, 2020)
Metascience refers to the systematic process that uncovers, builds, evaluates, organizes and disseminates scientific advances. It is the principal tool at the disposal of the society to combat the debilitating effects of “false information” on health related data and its constituents.